2014
DOI: 10.1136/jnnp-2013-307072
|View full text |Cite
|
Sign up to set email alerts
|

An MRI review of acquired corpus callosum lesions

Abstract: Lesions of the corpus callosum (CC) are seen in a multitude of disorders including vascular diseases, metabolic disorders, tumours, demyelinating diseases, trauma and infections. In some diseases, CC involvement is typical and sometimes isolated, while in other diseases CC lesions are seen only occasionally in the presence of other typical extra-callosal abnormalities. In this review, we will mainly discuss the MRI characteristics of acquired lesions involving the CC. Identification of the origin of the CC les… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(52 citation statements)
references
References 25 publications
0
50
0
1
Order By: Relevance
“…These data are useful for differentiating MS lesions-which typically affect the inferior corpus callosum in an asymmetrical distribution-from vascular lesions. 83 Single-slab is otropic 3D T2-FL AIR (voxel size = 1 mm 3 ) could replace 2D T2-FLAIR sequences, as it combines the advantages of a single-slab mode and high spatial resolution, in an acquisition time appropriate for routine examination of patients (when long echo-train acquisition is used, and in combination with parallel imaging). In some studies, 3D T2-FLAIR has shown better performance than 2D T2-FLAIR for detecting MS lesions, possibly owing to the large number of thin contiguous slices acquired and the increased contrast-to-noise ratio.…”
Section: T2-weighted Sequencesmentioning
confidence: 99%
“…These data are useful for differentiating MS lesions-which typically affect the inferior corpus callosum in an asymmetrical distribution-from vascular lesions. 83 Single-slab is otropic 3D T2-FL AIR (voxel size = 1 mm 3 ) could replace 2D T2-FLAIR sequences, as it combines the advantages of a single-slab mode and high spatial resolution, in an acquisition time appropriate for routine examination of patients (when long echo-train acquisition is used, and in combination with parallel imaging). In some studies, 3D T2-FLAIR has shown better performance than 2D T2-FLAIR for detecting MS lesions, possibly owing to the large number of thin contiguous slices acquired and the increased contrast-to-noise ratio.…”
Section: T2-weighted Sequencesmentioning
confidence: 99%
“…The majority of vascular lesions noted in this study involved the splenium of the CC, which has been reported previously in smaller series as well [6,11]. This may reflect the slightly higher incidence of infarcts in the posterior cerebral artery versus anterior cerebral artery territory, although both are relatively rare, with anterior cerebral artery infarction accounting for only 0.6-3 % of all infarcts, [16,18,20,22] and posterior cerebral artery infarction accounting for 7-14 % of all infarcts [18,20].…”
Section: Discussionmentioning
confidence: 54%
“…The majority of tumors identified were primary CNS tumors such as glioblastoma multiforme or lymphoma, both of which commonly invade the CC [11]. Nonvascular CC lesions were more likely to have concomitant cortical T2/ FLAIR hyperintensities and be associated with gadolinium enhancement and mass effect on MRI, all of which are radiographic features often associated with CNS tumors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Transient splenial lesions may also be a consequence of posterior reversible encephalopathy syndrome, the etiology of which includes hypertension and toxic/metabolic disturbance, radiation induced leukoencephalopathy, and recent seizures. In-born errors of metabolism and hereditary leukodystrophies may also involve the splenium, but diffuse involvement of other regions is present as well [1]. …”
Section: Cerebral Vasospasm Manifesting As a Transient Lesion Of The mentioning
confidence: 99%